2009
DOI: 10.1002/atr.5670430305
|View full text |Cite
|
Sign up to set email alerts
|

Cellular automata model for heterogeneous traffic

Abstract: Cellular Automata (CA) modelling is extended to study the heterogeneous traffic observed in developing countries. In heterogeneous traffic, the physical and mechanical characteristics of different vehicles vary widely which in turn leads to complex traffic behaviour resulting in no-lane discipline. This nature of the heterogeneous traffic is modelled with the help of an improved discrete CA model. A detailed description of the methodology used in developing the basic structure of the CA model is presented and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 21 publications
(29 reference statements)
0
47
0
Order By: Relevance
“…Authors (Lan and Chang, 2005;Vasic and Ruskin, 2012) developed models with two modes of traffic for multilane traffic flow. Subsequently many developments have taken place with the introduction of several modes of traffic to simulate various kinds of traffic flow situations (Mathew et al, 2006;Meng and Weng, 2011;Mallikarjuna and Rao, 2009). To consider natural human behaviour in simulation model randomization parameter is used, this parameter includes situations in which driver reduces the speed for example some incidents on road that diverts drivers attention.…”
Section: Work Zone Optimization Using Simulationmentioning
confidence: 99%
“…Authors (Lan and Chang, 2005;Vasic and Ruskin, 2012) developed models with two modes of traffic for multilane traffic flow. Subsequently many developments have taken place with the introduction of several modes of traffic to simulate various kinds of traffic flow situations (Mathew et al, 2006;Meng and Weng, 2011;Mallikarjuna and Rao, 2009). To consider natural human behaviour in simulation model randomization parameter is used, this parameter includes situations in which driver reduces the speed for example some incidents on road that diverts drivers attention.…”
Section: Work Zone Optimization Using Simulationmentioning
confidence: 99%
“…The longitudinal movement rules used in the study are similar to those proposed by Mallikarjuna and Rao [12] for heterogeneous conditions but with some modifications. In this model, originally based on Knospe's brake light model [9], the subject vehicle would react to the 'brake light status' of the leader vehicle.…”
Section: Longitudinal Movement Rulesmentioning
confidence: 99%
“…Matthew et al [11] proposed a modified cell size, randomisation rule and lane-changing rule of CA model for heterogeneous conditions. Mallikarjuna and Rao [12] (Ma-Ra) developed a heterogeneous traffic model for Indian conditions. They found that traffic in India is highly heterogeneous with frequent lane changing; hence, it was necessary to modify the Knospe's model to incorporate many types of vehicles and also their lateral movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1]Cellular automaton is mathematical model in which time,space and other variables are all discrete.…”
Section: The Mbt Model Based On Cellular Automatonmentioning
confidence: 99%